Per una laborialità artistica dei media locativi: il caso Karosta (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
Since the early 1990s, the advent of mobile media and portable geolocation devices has introduced a new approach to the digitization of space and its real-time representation. This development has enabled artists to incorporate their physical performance into a complex and situated system. The paper presents an investigation of the Locative Media Workshop, held in Karosta, a small Latvian town on the Baltic Sea, in the summer of 2003. The first workshop established the creative trend of locative media, which is based on collaborative practices in public space. The text not only reconstructs the execution of the event at the RIXC Center for New Media Culture in Riga but also focuses on how this laboratory-based, exploratory, and participatory approach marked a significant evolution from earlier forms of networked media art.